Short fictional biography. Posibility of a reader’s literary genre - Sousa, Rafael Andugar (2018)
In this article, we begin from the theoretical implications vislumbrated by J. M.Schaeffer with the porpose to create a new literary genre based in the task of the reader to compare diverse literary works which maybe don’t belong to the same tradition. The object of our interest is the existence of tales and narrations of biographies which are invented by an author interested in real historical characters (or even also invented). To explore the limits of the genre is necessary to know deeply the field of biografphy and the relations with literary writing and the relations with historiographical discourse too.